341 Ovarian cancer care at a hospital with an igcs global curriculum fellowship. (18th September 2019) - Tran, Q; Ng, J; Van Le, L; DeStephano, C; Tran, Q; Dinh, T; Vo, TH
Abstract : Objectives: To determine the impact of implementation of an IGCS global curriculum fellowship on cancer care. Methods: We performed a retrospective review of consecutive ovarian cancer cases treated since the start of the IGCS Global Curriculum fellowship on July, 2017 and March, 2019 at Danang Oncology Hospital (DOH). There were 2 groups of patients- those who underwent surgery for ovarian cancer at a general hospital then referred to DOH and those who were diagnosed and treated at DOH primarily. Clinical parameters of the 2 groups were compared. Chi-Squared analysis was used to compare the 2 groups. Results: Between July, 2017 and March, 2019, 65 consecutive ovarian cancer cases were treated at DOH. 27 patients were initially treated at a general hospital and referred, and 38 patients were diagnosed and treated at DOH. Correct diagnosis was rendered in 55% of referred patients compared to 97% of patients diagnosed initially at DOH (p=0.000003). Correct staging surgery was done in 7.4% of referred patients compared to 42% of patients operated primarily at DOH (p<0.000001). There was a trend towards optimal debulking favoring DOH. Time to chemotherapy did not differ between the 2 groups. Germ cell tumors were more likely to be diagnosed at a general hospital than at DOH (p=0.04). Conclusions: Receiving care for ovarian cancer at a hospital affiliated with IGCS Global Curriculum Fellowship more often resulted in correct diagnosis and surgery. There are still opportunities to improve. There is a need to educate non oncology surgeons about clinical presentation of adnexal masses in the young patient.